Answer:
b. x + (x + 2) + (x + 4) = 39
Step-by-step explanation:
<u>Definitions</u>
- Integer: a whole number that can be positive, negative or zero.
e.g. ..., -3, -2, -1, 0, 1, 2, 3, ... - Odd number: an integer that when divided by two leaves a remainder (so not a multiple of 2). For example, 1, 3, 5, 7 are all positive odd numbers.
- Consecutive: following one after the other in order.
<u>The sum of three consecutive odd integers</u>
Let x be the first odd integer.
As there is a <u>difference of 2</u> between <u>consecutive odd integers</u>, the next odd integer after x will be (x + 2).
Therefore, the next odd integer after (x + 2) will be (x + 2) + 2 = (x + 4).
So "the sum of three consecutive odd integers is thirty-nine" is:
x + (x + 2) + (x + 4) = 39
<u>To solve</u>
⇒ x + (x + 2) + (x + 4) = 39
⇒ x + x + 2 + x + 4 = 39
⇒ 3x + 6 = 39
⇒ 3x = 33
⇒ x = 11
Therefore, the three consecutive odd numbers are 11, 13 and 15.